The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s40104-022-00721-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mitigation option of greenhouse gas emissions from lactating Holstein dairy cows in East China

Abstract: Background This study investigated greenhouse gas (GHG) emission characteristics of lactating Holstein dairy cows in East China and provided a basis for formulating GHG emission reduction measures. GreenFeed system was used to measure the amount of methane (CH4) and carbon dioxide (CO2) emitted by the cows through respiration. Data from a commercial cow farm were used to observe the effects of parity, body weight, milk yield, and milk component yield on CH4 and CO2 emissions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Per capita milk consumption in China is much lower than the global level, and vigorous efforts are still needed to develop the dairy industry. Consequently, mitigation strategies for China’s dairy industry need to be extensively investigated [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Per capita milk consumption in China is much lower than the global level, and vigorous efforts are still needed to develop the dairy industry. Consequently, mitigation strategies for China’s dairy industry need to be extensively investigated [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to rapid economic growth, China became the world’s largest GHG emitter, surpassing US emission levels in 2006 [ 93 ]. However, recently, China has increased awareness of the harmfulness of GHGs and taken measures to address them [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Enteric CH 4 and CO 2 emissions and O 2 consumption were measured using two sets of the GreenFeed Large Animal System (product No. 157 and 158; C-Lock, Inc., Rapid City, SD, USA) as described by Jia et al [ 22 ]. Generally, 10 Jersey cows from each treatment (40 cows in total) were randomly selected and trained for 10 d to adapt the GreenFeed systems before the commencement of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the carbon emissions associated with animal husbandry in the three central Chinese provinces, some researchers have employed the carbon emission coe cient approach. One study found that large livestock, such as pigs, cattle, and sheep, are the main emission sources of animal husbandry (Jia et al 2022). However, these emission sources remain unknown.…”
Section: Literature Reviewmentioning
confidence: 99%